IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III DI SDN KARANG MULYA 1 KOTA TANGERANG - Nur Aliza Sefani; Romi Ramdon Ginanjar; Arry Patriasurya Azhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education in Indonesia continues to evolve, with the Merdeka Curriculum emerging as a response to the need for flexible, relevant, and student-centered learning. Yet, its implementation in schools is not without challenges. Teachers often struggle with understanding the curriculum structure, planning effective lessons, and applying appropriate assessments. This study focuses on the implementation of the Merdeka Curriculum in the third-grade Indonesian language class at SDN Karang Mulya 1, Tangerang City. Using a descriptive qualitative approach, data were collected through observations, interviews, and documentation. The findings reveal that teachers have grasped the foundation of the Merdeka Curriculum, prepared lesson plans aligned with its principles, and delivered contextual as well as differentiated learning activities. Assessments were carried out diagnostically, formatively, and summatively, though understanding of authentic assessment still needs improvement. School facilities have supported the process, ensuring smoother implementation. In conclusion, the Merdeka Curriculum is on the right track in this school, yet strengthening teacher competence remains essential for future success.